Ten undescribed diterpenoid quinones derived from the Salvia miltiorrhiza. (August 2022) - Ren, Ying-Jie; Cao, Yan-Gang; Zeng, Meng-Nan; Zhang, Qin-Qin; Liu, Yan-Ling; He, Chen; Chen, Xu; Fan, Xi-Ling; Li, Xiang-Da; Zheng, Xiao-Ke; Feng, Wei-Sheng
Abstract: This study aimed to report the structure elucidation of the compounds isolated from Salvia miltiorrhiza, and their biological evaluations. Ten undescribed diterpenoid quinones and 10 known analogues were isolated from the dried roots of S. miltiorrhiza . Their structures were elucidated by extensive analysis, including nuclear magnetic resonance, high-resolution mass spectra, and ultraviolet and infrared spectra. Their absolute configurations were determined by comparing the experimental and calculated electronic circular dichroism spectra. In the evaluation of bioactivities, Salvianolactone acid I, epi -danshenspiroketallactone F, danshinspiroketallactone, grandifolia G, and 2 H -Naphtho [1, 8- bc ]furan (10 μM) significantly increased cell viability and decreased the nuclear transport of p-P65 in lipopolysaccharide-induced bronchial epithelial cells. It was concluded that the diterpenoid quinones might belong to potent targeted lung-protective agents. Graphical abstract: Ten undescribed diterpenoid quinones were isolated from the dried roots of S. miltiorrhiza . Image 1 Highlights: Ten undescribed diterpenoid quinones were isolated from the dried roots of Salvia miltiorrhiza. Their structures were elucidated by NMR and mass spectrometry. All the isolated compounds were evaluated in vitro for their lung-protective effects.